KAJIAN PRINSIP KONSERVASI DALAM PENGELOLAAN HUTAN DAN LAHAN DI KABUPATEN SEMARANG - , Muhamad Syafardi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Semarang District is one district in Central Java province has a forest area with a fully functional forest the production, protection and conservation, forest and land issues in Semarang district is the high attrition rate can regard Rawapening reservoir water volume in 2000 is 45,930 .578 m3 shrinkage compared to the baseline calculation in 1976 that as many as 65 million m3. So the need for intensive treatment on the sedimentation process upstream, in 2021's supposed sludge sedimentation Rawapening closed surface. In connection with this research aimed to identify the characteristics of the land and forest resources in forest areas and lands outside the forest area in the district of Semarang include: soil type, slope of land / tofografi and altitude above sea level as well as reviewing the principle of conservation of forest management and land cover and land use aspects of forest, land and forest resources aspects, aspects of policy / institutional and community empowerment aspects. he research method used is the method suevey Semarang District is divided into four regions based on the level of implementation in conservation. Each area was evaluated by using a rule p.38 2009 on the Standards and Guidelines for Assessment of Forest Management Bekelanjutan (Lestari) that rank well with the number 3 (three), quite a number (2) and bad with numbers (1). The principle of conservation assessment has a score (42 -63) means well, the score (21-42) means pretty, scores 1-21 means ugly, method of data collection empowerment using RRA (Rapid Rural Appraisal) and PRA (Partisipaspatory Rural Appraisal). Furthermore, based on primary data and secondary data was carried out studies of forest management and land conservation. Society has applied the principle of conservation criteria in the management of the community forest is the result sustainability, Clarity about land tenure or forest area used and principles of forest ecosystem stability can be maintained and disruption to it can be minimized and managed. Keeping keletarian community forest resources, farmers' groups have applied the principles of sustainability resource conservation, assured security and economic development community. In the principle of conservation policy / institutional, farmer groups have applied clarity on property rights and land management or forest areas are used, ensuring resilience and community economic development. Empowerment of the people in the forest, farmers' groups have applied the principles of sustainability of conservation efforts, the establishment of a similar pattern of social relations in the production process, and the benefits in the interests of justice community.